Milkfish supply chain in Burauen, Leyte - Gaspay, Ivy A.; Laloces, Frences Girly Joy A.; Retales, Mary Grace R.
This research was designed to map out and examine the prevailing milkfish supply chain map in Burauen, Leyte, involving five milkfish sellers from Burauen Fish Market (BFM) and seven non-registered milkfish sellers from Burauen Talipapa Market (BTM). Data were collected through primary sources including survey questionnaires, one-on-one interviews, and information from the municipal market head office. The sociodemographic analysis revealed that BFM sellers were generally older with longer experience, while both markets were composed of married female sellers. Findings also highlighted significant disparities between the markets: BTM handled larger volumes of milkfish, resulting in higher sales and revenue, but also higher operational costs. Major challenges identified across both markets were limited supply, insolvent customers, poor milkfish quality, and insufficient capital. This research provides an up-to-date overview of the milkfish market dynamics and valuable insights regarding the milkfish supply chain in Burauen, Leyte, specifically in the trading and importation stage of the chain.